Movement‐based interventions for preschool‐age children with, or at risk of, motor impairment: a systematic review. (12th November 2019) - Cameron, Kate L; Albesher, Reem A; McGinley, Jennifer L; Allison, Kim; Cheong, Jeanie L Y; Spittle, Alicia J
Abstract : Aim: To explore the efficacy of movement‐based interventions to improve motor skills in preschool‐age children with, or at risk of, motor impairment, including those with a diagnosis of cerebral palsy, autism spectrum disorder, and developmental coordination disorder. Method: Relevant electronic databases were searched for randomized or quasi‐randomized controlled trials. Outcomes were classified using domains of the International Classification of Functioning, Disability and Health: Children & Youth version. Quality was assessed using the Physiotherapy Evidence Database scale. Risk of bias was assessed using the Cochrane Risk of Bias tool. Effect sizes were calculated using Cohen's d . Results: Seventeen articles exploring a heterogeneity of intervention types, population groups, and outcome measures met the inclusion criteria. Movement‐based interventions did not significantly improve outcomes in either the body structure and function or activity domains in most studies. No studies used a participation outcome measure. Interpretation: There is a paucity of evidence exploring movement‐based interventions in the preschool‐age group. Although movement‐based interventions showed potential for improving body structure and function and activity outcomes for children with motor impairment, results were mostly not significant. Small sample sizes, variable study quality, and risk of bias limit confidence in the results. What this paper adds: The evidence is inconclusive to support movement‐based interventions in this group. No studies used outcome measures assessing participation. Variability in intervention type and study quality limit confidence in results. What this paper adds: The evidence is inconclusive to support movement‐based interventions in this group. No studies used outcome measures assessing participation. Variability in intervention type and study quality limit confidence in results. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Intervenciones basadas en el movimiento para niños con discapacidad motora o de riesgo en edad preescolar: una revisión sistemática: Objetivo: Explorar la eficacia de las intervenciones basadas en el movimiento para mejorar las habilidades motoras en niños con deficiencia motora, o de riesgo, en edad preescolar incluidos aquellos con diagnóstico de parálisis cerebral, trastorno del espectro autista y trastorno del desarrollo de la coordinación. Metodo: Se realizaron búsquedas en bases de datos electrónicas relevantes para ensayos controlados aleatorios o cuasi‐aleatorios. Los resultados se clasificaron utilizando dominios de la Clasificación Internacional del Funcionamiento, de la Discapacidad y de la Salud: versión para Niños y Jóvenes. La calidad se evaluó mediante la Physiotherapy Evidence Database scale. El riesgo de sesgo se evaluó mediante la herramienta Cochrane de riesgo de sesgo. Los tamaños del efecto se calcularon usando el Cohen's d . Resultados: Diecisiete artículos que exploran una heterogeneidad de los tipos de intervención, grupos de población y medidas de resultado cumplieron con los criterios de inclusión. Las intervenciones basadas en el movimiento no mejoraron significativamente los resultados ni en la estructura corporal ni en los dominios de función o actividad en la mayoría de los estudios. Ningún estudio utilizó una medida de resultado de participación. Interpretacion: Hay escasez de pruebas que exploren las intervenciones basadas en el movimiento en el grupo de edad preescolar. Aunque las intervenciones basadas en el movimiento mostraron potencial para mejorar la estructura corporal y los resultados de la función y la actividad para los niños con discapacidad motriz, los resultados no fueron significativos. Los tamaños de muestra pequeños, la variabilidad de calidad de los estudios y el riesgo de sesgo limitan la confianza en los resultados. Resumo: Intervenções baseadas no movimento para crianças em idade pré‐escolar com, ou de risco para, deficiência motora: uma revisão sistemática: Objetivo: Explorar a eficácia de intervenções baseadas no movimento para melhorar habilidades motoras em crianças de idade pré escolar com, ou de risco para, deficiência motora, incluindo aquelas com diagnóstico de paralisia cerebral, transtorno do espectro autista, e transtorno do desenvolvimento da coordenação. Método: Bases de dados eletrônicas relevantes foram pesquisadas quanto a estudos randomizados ou quasi‐randomizados controlados. Os resultados foram classificados usando domínios da Classificação Internacional de Funcionalidade, Incapacidade e Saúde: versão Crianças & Jovens. A qualidade foi avaliada usando a escala da Base de Dados de Evidência em Fisioterapia. O risco de viés foi avaliado usando o instrumento Cochrane de Risco de viés. Tamanhos de efeito foram calculados usando d de Cohen. Resultados: Dezessete artigos explorando a heterogeneidade dos tipos de intervenção, grupos populacionais, e medidas de resultado atenderam aos critérios de inclusão. Intervenções baseadas no movimento não melhoraram sigificativamente os resultados nos domínios de estrutura e função do corpo ou atividade na maioria dos estudos. Nenhum estudo usou a participação como medida de resultado. Interpretação: Há escassez de evidências explorando intervenções baseadas no movimento na faixa etária pré‐escolar. Embora intervenções baseadas no movimento mostrem potencial para melhorar resultados de estrutura e função do corpo e atividade para crianças com deficiência motora, os resultados em sua maior parte não foram significantes. Pequenos tamanhos amostrais, qualidade variável dos estudos, e risco de viés limitam a confiança nos resultados.